The Impact of Non-Performing Loans (NPL) and Loan-to-Deposit Ratio (LDR) on the Profitability of Conventional Commercial Banks Listed on the Indonesia Stock Exchange - Yulyanti, Sinta; Jamil, Poppy Camenia; Habillah, Janatri; Abdullah, Siti Intan Nurdiana Wong (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study examines the effect of Non-Performing Loans (NPL) and Loan-to-Deposit Ratio (LDR) on Return on Assets (ROA) in the banking sector on the Indonesia Stock Exchange over a period of 10 years, from 2011 to 2020. The analysis uses panel data from 14 conventional commercial banks listed on the IDX, with a total of 138 observations spanning from 2011 to 2021. Static panel data regression is employed for the analysis. The results indicate that the NPL variable has a significant negative effect on ROA, with a probability value of 0.0002, which is smaller than the 5% significance level. The coefficient of -0.253098 suggests that a 1% increase in NPL leads to a 0.253098% decrease in ROA. This finding implies that higher levels of non-performing loans negatively impact bank profitability by slowing down bank operations. In extreme cases, increased bad debts could reduce a bank's ability to guarantee public funds, potentially leading to systemic risk.